2005
DOI: 10.2223/jped.1391
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of multicystic dysplastic kidney: clinical course and ultrasound outcome

Abstract: Objective: The aim of this study was to describe the clinical course and ultrasound outcome of prenatally detected multicystic dysplastic kidney.Methods: Fifty-three children with unilateral multicystic dysplastic kidney detected by prenatal ultrasound between 1989 and 2004 were included in the analysis. All children were submitted to conservative management with follow-up visits every six months. Follow-up ultrasound examinations were performed at six-month intervals during the first two years of life and yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In our study, follow-up sonograms showed complete involution or regression in the majority of the MCDKs (70.6%) while demonstrating no size increase in the rest of them (29.4%), which helped the clinicians avoid unnecessary nephrectomies. The consequences of long-term followups in pediatric patients with MCDKs demonstrate that conservative management under US control is reliable also for the contralateral kidney [36]. As an example, Kuwertz-Broeking et al [10] reported the dilatation of the urinary tract on the contralateral side to be present in 12% of the 97 children with MCDKs children included in the study, which was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, follow-up sonograms showed complete involution or regression in the majority of the MCDKs (70.6%) while demonstrating no size increase in the rest of them (29.4%), which helped the clinicians avoid unnecessary nephrectomies. The consequences of long-term followups in pediatric patients with MCDKs demonstrate that conservative management under US control is reliable also for the contralateral kidney [36]. As an example, Kuwertz-Broeking et al [10] reported the dilatation of the urinary tract on the contralateral side to be present in 12% of the 97 children with MCDKs children included in the study, which was similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…US was declared to be the most suitable tool for the initial evaluation of children with MCDK [33], while the primary approach to the patients with MCDK was reported to be conservative follow-ups by utilizing US [20,34,35]. Though an overt tendency for MCDK to show a timedependent regression in size has been reported [36], the results of the long-term study conducted by Aslam et al [35] revealed that in 41% of the children with unilateral MCDK, renal remnants still persist 10 years after the initial diagnosis, which justifies the need for sonographic follow-ups. Nephrectomy was the usual treatment for unilateral MCDKs in the past; however, due to the high incidence of spontaneous regression and involution, a conservative and clinical management is preferred today [4,25,26], which includes yearly clinical evaluations and US examinations with increased intervals [20].…”
Section: Discussionmentioning
confidence: 99%
“…This is less frequent than the reported range of 45–77% 24 25 26. Using the more common and less stringent definition of only a single measurement exceeding the 95% CI, 61% of our “single kidneys” qualify for compensatory renal hypertrophy.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies have shown that conservative management seems to be a safe option; the prevalence of complications is negligible and most of the affected units have partial or complete involution on US. Recently, a comparative study between surgical and conservative treatments has not revealed any significant difference in the frequency of complications for the patients (30).…”
Section: Discussionmentioning
confidence: 99%